Regulation of ascorbate-glutathione cycle by exogenous nitric oxide and hydrogen peroxide in soybean roots under arsenate stress - Singh, Samiksha; Husain, Tajammul; Kushwaha, Bishwajit Kumar; Suhel, Mohammad; Fatima, Abreeq; Mishra, Vipul; Singh, Sani Kumar; Bhatt, Javaid Akhtar; Rai, Meena; Prasad, Sheo Mohan; Dubey, Nawal Kishore; Chauhan, Devendra Kumar; et al. (My University, 2021)
The role of nitric oxide (NO) and hydrogen peroxide (H2O2) is well known for regulating plant abiotic stress responses. However, underlying mechanisms are still poorly understood. Therefore, the present study investigated the involvement of NO and H2O2 signalling in the regulation of arsenate toxicity (AsV) in soybean roots employing a pharmacological approach. Results show that AsV toxicity declined root length and biomass due to greater As accumulation in the cell wall and cellular organelles. Arsenate induced cell death due to enhanced levels of reactive oxygen species, lipid and protein oxidation and down-regulation in ascorbate-glutathione cycle and redox states of ascorbate and glutathione. These results correlate with lower endogenous level of NO. Interestingly, addition of L-NAME increased AsV toxicity. However, addition of SNP reverses effect of L-NAME, suggesting that endogenous NO has a role in mitigating AsV toxicity. Exogenous H2O2 also demonstrated capability of alleviating AsV stress, while NAC reversed the protective effect of H2O2. Furthermore, DPI application further increased AsV toxicity, suggesting that endogenous H2O2 is also implicated in mitigating AsV stress. SNP was not able to mitigate AsV toxicity in the presence of DPI, suggesting that H2O2 might have acted downstream of NO in accomplishing amelioration of AsV toxicity.
Keywords: Ascorbate-glutathione cycle; Cell death; Oxidative stress; Root growth; Sequestration; Vacuolar